Do continuity Marketing, one-to-one marketing, Partnering Programs and Corporate Social Responsibility Define Customer Loyalty of a Bank Company? The Intervening Role of Customer Satisfaction - Sutarmin, Sutarmin; Irsalina, Hany; Sugiyanto, Sugiyanto; Budiarti, Wiwik (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2024)
Customer loyalty is an important factor for the success of the banking industry, both to create short-term and long-term profits in terms of finances and company reputation. This research was then aimed at analysing the influence of continuity marketing, one-to-one marketing, partnering programs, and corporate social responsibility on customer loyalty and the role of customer satisfaction as a mediator in this relationship. This research used a quantitative approach, with the chosen population being all customers who use all types of products or services at Bank Jatim Main Branch Surabaya. The sample determined was 250 samples, selected using purposive sampling. Research data was obtained through a survey mechanism, and the research data was then analysed using PLS-SEM (Partial Least Square - Structural Equation Modeling). The results of data analysis showed that continuity marketing, partnering programs, and corporate social responsibility had a significant effect on customer satisfaction, while one-to-one marketing did not have a significant effect on customer satisfaction. Furthermore, continuity marketing, one-to-one marketing, partnering programs, corporate social responsibility, and customer satisfaction significantly affect customer loyalty. This research also proved that customer satisfaction can mediate the influence of continuity marketing and corporate social responsibility on customer loyalty.